Pengukuran Efektivitas Mesin dengan Metode Overall Equipment Effectiveness Pada Mesin Stamping - Vallerina Lawrencia Tertaroza; Deri Teguh Santoso; Reza Setiawan; Jojo Sumarjo (Jurnal Serambi Engineering, 2023)
The ability of an industrial company to produce a product will certainly depend on the ability of the machine used as a tool to produce every part of the product. Over time, increased market demand must be accompanied by an increase in production rates. Where this requires industrial companies to have high productivity, especially in the machining parts used in the production process. We can measure this effectiveness using the Overall Equipment Effectiveness (OEE) method, which is often used to measure the productivity of the machine or equipment used. Based on the research results, it can be seen that the average value of Overall Equipment Effectivities (OEE) on a stamping machine is 39.9%.